1960
DOI: 10.1677/joe.0.0210197
|View full text |Cite
|
Sign up to set email alerts
|

Bone Structure and Metabolism in Calcium-Deficient Rats

Abstract: Pure calcium deficiency produces osteoporosis, or bone atrophy, in rats, while vitamin D deficiency as well as calcium deficiency leads to osteomalacia, or thin bones with wide osteoid seams. The retention of a dose of strontium in the osteoporotic rats is greater than normal, and this indicates rapid bone formation. The immediate cause of the bone thinning must therefore be an increase in the rate of bone resorption, contrary to the classical concepts of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Indeed, only when increased 1,25(OH) 2 D levels could elicit a skeletal response [i.e., in Vdr int-mice, 1,25(OH) 2 Dtreated Vdr oc+ mice, and Vdr int+ mice receiving a low-calcium diet, but not in Vdr -/-or Vdr oc-mice] was bone matrix mineralization inhibited, and was a profound shift of calcium from bone to serum observed. In agreement with this finding, bone fractures that are associated with dietary calcium restriction in growing rats are prevented when the low-calcium diet is combined with vitamin D deficiency, but the latter condition is associated with more pronounced hypocalcemia (4). Several lines of evidence support our finding that increased 1,25(OH) 2 D serum levels suppresses bone matrix mineralization.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, only when increased 1,25(OH) 2 D levels could elicit a skeletal response [i.e., in Vdr int-mice, 1,25(OH) 2 Dtreated Vdr oc+ mice, and Vdr int+ mice receiving a low-calcium diet, but not in Vdr -/-or Vdr oc-mice] was bone matrix mineralization inhibited, and was a profound shift of calcium from bone to serum observed. In agreement with this finding, bone fractures that are associated with dietary calcium restriction in growing rats are prevented when the low-calcium diet is combined with vitamin D deficiency, but the latter condition is associated with more pronounced hypocalcemia (4). Several lines of evidence support our finding that increased 1,25(OH) 2 D serum levels suppresses bone matrix mineralization.…”
Section: Discussionsupporting
confidence: 89%
“…The action of 1,25(OH) 2 D therefore seems to be important in the normal skeletal responses that prevent hypocalcemia during a negative calcium balance. Previous dietary studies have shown that the amount of calcium stored in bone declines when dietary calcium supply is insufficient (4). However, the molecular skeletal adaptations that redirect calcium from bone to serum are still not identified.…”
Section: Introductionmentioning
confidence: 99%
“…Harrison and Fraser (22) reported that a low-calcium diet (8 mg/100 g; 0.008%) produces osteoporosis or bone atrophy in rats. They suggested that pure calcium deficiency leads to osteoporosis, while vitamin D deficiency together with calcium deficiency produces osteomalacia in these rats.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction Under the culture condition, nodules with characteristics of normal bone appeared by day 30 regardless Animals fed with a low calcium diet develop osteopoof the calcium conditions. However, the low calcium rosis and bone atrophy [1], and an increase in plasma environment enhanced the mRNA expressions of c-fos, alkaline phosphatase (ALP) activity [2,3]. Earlier we c-jun and osteocalcin, a specific marker of the osteoblast conjectured that a low calcium environment might be phenotype.…”
mentioning
confidence: 99%